2014
DOI: 10.1126/science.1246949
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Activity Conditions the Effect of Regulatory Variants upon Monocyte Gene Expression

Abstract: To systematically investigate the impact of immune stimulation upon regulatory variant activity, we exposed primary monocytes from 432 healthy Europeans to interferon-γ (IFN-γ) or differing durations of lipopolysaccharide and mapped expression quantitative trait loci (eQTLs). More than half of cis-eQTLs identified, involving hundreds of genes and associated pathways, are detected specifically in stimulated monocytes. Induced innate immune activity reveals multiple master regulatory trans-eQTLs including the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
879
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 732 publications
(980 citation statements)
references
References 83 publications
52
879
2
Order By: Relevance
“…Indeed, different association studies have identified IRF8-and/or IRF1-associated variants as genetic risk factors for inflammatory bowel disease, multiple sclerosis, rheumatoid arthritis, and other chronic inflammatory diseases in humans (Jostins et al, 2012;Beecham et al, 2013;Okada et al, 2014). Of interest is a single nucleotide polymorphism near IRF8 (SNP accession number rs17445836) that regulates IRF8 mRNA expression (eSNP) in peripheral blood mononuclear cells and that is also the lead risk factor single nucleotide polymorphism associated with multiple sclerosis (Fairfax et al, 2014). Likewise, a similar regulatory single nucleotide polymorphism located near IRF1 behaves as a risk factor for Crohn's disease (Fairfax et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, different association studies have identified IRF8-and/or IRF1-associated variants as genetic risk factors for inflammatory bowel disease, multiple sclerosis, rheumatoid arthritis, and other chronic inflammatory diseases in humans (Jostins et al, 2012;Beecham et al, 2013;Okada et al, 2014). Of interest is a single nucleotide polymorphism near IRF8 (SNP accession number rs17445836) that regulates IRF8 mRNA expression (eSNP) in peripheral blood mononuclear cells and that is also the lead risk factor single nucleotide polymorphism associated with multiple sclerosis (Fairfax et al, 2014). Likewise, a similar regulatory single nucleotide polymorphism located near IRF1 behaves as a risk factor for Crohn's disease (Fairfax et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies could test this hypothesis, as eQTL data for large numbers of different cell types become increasingly available. Recently two studies identified eQTLs under LPS stimulation in primary human monocytes 29 and dendritic cells 30 . Comparison of our study with these studies showed a significant overlap between our data and those of Fairfax et al 29 In all, 43 and 44% of our monocyte data under baseline and LPS stimulation, respectively, were found to be genome-wide significant in Fairfax et al (Supplementary Fig.…”
Section: δLps/baselinementioning
confidence: 99%
“…Recently two studies identified eQTLs under LPS stimulation in primary human monocytes 29 and dendritic cells 30 . Comparison of our study with these studies showed a significant overlap between our data and those of Fairfax et al 29 In all, 43 and 44% of our monocyte data under baseline and LPS stimulation, respectively, were found to be genome-wide significant in Fairfax et al (Supplementary Fig. 9a) and 55 (baseline) and 56% (LPS) of the data of Fairfax et al showed evidence of replication in our data set ( Supplementary Fig.…”
Section: δLps/baselinementioning
confidence: 99%
“…Notably, the 7 h LPS samples were most distant (least correlated with) from the control samples. In keeping with evidence that LPS‐inducible genes in monocytes can be treated as quantitative traits with extensive variation between individuals,51 samples from the same donor tended to be in the same neighborhood.…”
Section: Resultsmentioning
confidence: 53%
“…LPS is itself known to induce type 1 IFNs (mainly IFNβ) in MDM, which act in an autocrine manner via IFNAR1, itself induced by LPS 27. Accordingly, the response to exogenous type 1 IFN (IFNα) was largely a subset of the LPS response, as reported in previous studies 24, 28, 50, 51, 54. None of the anti‐inflammatory agents we examined completely prevented the response to either challenge and, although prednisolone and anti‐TNFα both reduced expression of many genes that were up‐ or down‐regulated by the inflammatory challenges, each had a distinctive transcriptional effect.…”
Section: Discussionmentioning
confidence: 59%